Nova tehnologija i pristup muzejskim zbirkama: iskustvo zagrebačkih umjetničkih muzeja i galerija - Vujić, Žarka (Array, 2000)
Nova tehnologija i pristup muzejskim zbirkama: iskustvo zagrebačkih umjetničkih muzeja i galerija